From the Earth - Tidwell, Tia (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2026)
This short lyrical reflection traces the layered meanings carried within my Inupiaq name, Puya—‘from the earth.’ Through memories of my aana and her sister, I explore how names connect us to those who came before. The narrative moves between childhood recollections, the weight of intergenerational survival, and the sacred responsibilities of care at the end of life. In witnessing death and remembering survival, I reflect on how carrying a name is also carrying love, grief, and obligation across time. This piece asks what it means to be known by one’s ‘real name’ and how names continue to release memory, presence, and kinship into the world.